PENINGKATAN KEAKTIFAN BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL ACTIVE LEARNING TIPE EVERYONE IS A TEACHER HERE - Agustiani, Dian Putri; Aziz, Noor; Firdaus (Institut Daarul Qur'an Jakarta, Indonesia, 2023)
The activeness of learning in the learning process is very important, one of the factors that causes the low activeness of learning mathematics in the learning process is the use of learning models. The purpose of this research is to find out the differences and increase in the activeness of learning mathematics using the active learning model of the everyone is a teacher here type. This type of research is Quasi Experimental Research with the Nonequivalent Control Group Design. The object of this research was the fourth grade students of MI Ma'arif Klesman with a population of 138 students. The sampling technique used purposive sampling, the Imam Ghazali class was selected as the experimental class and the Imam Shafi'i class as the control class. The research data was obtained through observation, questionnaires and documentation. The results showed (1) there was a difference in the increase in the activeness of learning mathematics between the experimental and control classes. This was evidenced by the results of the hypothesis test which showed t_count > t_table or 4.39 > 2.001 at the 5% significance level and 4.39 > 2.663 at the significance level 1%, 2) there is an increase in learning activity in the experimental class of 0.423 in the moderate category. So it can be concluded that the active learning model type everyone is a teacher here can increase the activeness of learning mathematics.